Wet Cough and Nasal Symptoms in Children: Can We Do Better? - de Benedictis, Fernando M.; Carloni, Ines; Comberiati, Pasquale; Shields, Michael D.; Bush, Andrew; Chang, Anne B. (Frontiers in Pediatrics, 2019)
The causes of chronic cough in children are mainly dependent on the setting and age of the child. Protracted bacterial bronchitis is a frequent cause of morbidity in childhood, and antibiotic treatment is beneficial. Prompt recognition and early treatment is important both to prevent inappropriate use of asthma medications and also progression to bronchiectasis, but the diagnosis should not be made uncritically, because chronic wet cough is not necessarily due to lower airway disease. Upper Airway Cough Syndrome (UACS) is considered by some to cause chronic cough in childhood. Underlying UACS are many common conditions, including allergic rhinitis, adenoiditis and rhinosinusitis. Diagnosis relies on a combination of clinical criteria that are relatively sensitive but non-specific. The role of nasal endoscopy in children with chronic cough and signs suggesting UACS is unclear. Nasal saline solution irrigation is commonly used in UACS, but most studies have methodological biases, and efficacy data are scanty. Randomized controlled trials are urgently required. However, if saline washes, rather than oral antibiotics, can effectively treat some children with wet cough, antibiotic resistance could potentially be reduced. There is a need to further study wet cough and not assumed to be equivalent to lower airway infection in all children.